2023
DOI: 10.1039/d3se00419h
|View full text |Cite
|
Sign up to set email alerts
|

Current state of biogas and biomethane production and its implications for Spain

M. Calero,
V. Godoy,
C. García Heras
et al.

Abstract: In recent years, Europe has tightened legislation to combat climate change. Among the new targets proposed by the different legal instruments, such as the European Green Deal, the Directives RED...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Finally, it should be pointed out that CO 2 captured at biogas plants can be used for various industrial applications, such as the syntheses of (I) polymers, (II) urea, (III) methanol and (IV) salicylic acid [118][119][120]. Furthermore, recent studies on this topic [37,[121][122][123] concluded that CO 2 captured from biogas, in combination with H 2 , can be applied for obtaining an additional CH 4 stream (hydrogenation process), according to the Sabatier reaction:…”
Section: H2smentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, it should be pointed out that CO 2 captured at biogas plants can be used for various industrial applications, such as the syntheses of (I) polymers, (II) urea, (III) methanol and (IV) salicylic acid [118][119][120]. Furthermore, recent studies on this topic [37,[121][122][123] concluded that CO 2 captured from biogas, in combination with H 2 , can be applied for obtaining an additional CH 4 stream (hydrogenation process), according to the Sabatier reaction:…”
Section: H2smentioning
confidence: 99%
“…Consequently, it allows to obtain biomethane with properties and a composition similar to those of natural gas [34] and meet the quality standards of natural gas grids [35]. It has been widely reported that effectively upgraded biogas, referred to as biomethane, should contain more than 95-97% CH 4 [14,[36][37][38][39][40][41]. Noteworthily, according to data presented in the International Energy Agency report [42], currently, 90% of biomethane produced worldwide is obtained by upgrading processes.…”
Section: Introductionmentioning
confidence: 99%
“…When processing biomass of plant origin into biogas, the components that make up fiber (structural carbohydrates and lignin) reduce the value of the raw material intended for biogas. Production of biomethane from organic waste and use for motor vehicle fuel is considered a priority area of bioenergy in the European Union [5].…”
Section: Introductionmentioning
confidence: 99%